The Analysis of the Process of Building an Integrated Management System - Marija Jurčević (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
An integrated management system is introduced when a company wants to achieve conformity of multiple norms with the aim of reducing the amount of paperwork, the time needed for assessment and the costs in construction and system maintenance. As the number of individual management systems has grown, the area where the standards overlap has expanded. This has prompted the need for the existing systems to integrate into one, unified system. An integrated management system can represent a very small, yet sufficiently large basis for building the business excellence, since it enables the organization to gradually shift the focus from buyers only onto all the participants. Many organizations opt for an integrated management system to encompass three key elements of management: quality, environmental protection and health and safety of the people. Bearing in mind that in today's turbulent business atmosphere organizations are choosing integrated systems more often, the purpose of this paper is to analyse the very process of integration of the management system. The integration of the management system provides the establishment of unique policy for managing a company. Based on the analysis of secondary data, the integration of the management system regarding the level and the degree of integration will be elaborated, along with the systematic approach to the integration of the management system. Management system integration is crucial if companies wish to achieve higher optimization and efficiency of their management.
Keywords: 650; horizontal integration; integrated management system; level of integration; management system; vertical integration